PTH-065 Diagnostic and Therapeutic Utility of Spyglass single Operator Peroral Cholangioscopy for Indeterminate Biliary Lesions: A Single Centre Experience in Scotland - Basavaraju, U; Fraser, A; Leeds, J (Gut, 2013)
IntroductionThe SpyGlass single-operator peroral cholangioscopy is a promising technique designed to overcome some of the limitations of conventional peroral cholangioscopy. We aimed to evaluate the diagnostic utility of the SpyGlass system in a cohort of patients with indeterminate biliary strictures and lesions. Methods All patients who were listed for SpyGlass cholangioscopy for for further evaluation or treatment of indeterminate strictures or filling defects previously identified at ERCP or other imaging modality were included in this study. After SpyGlass direct visual evaluation, targeted biopsies were taken with the SpyBite forceps and histopathological assessment was made by experienced gastrointestinal pathologists. Results Between April 2009 and January 2013, 21 subjects (mean age 60, 12 males) underwent SpyGlass cholangioscopy for indeterminate biliary strictures (n = 12) or filling defects (n = 9). SpyGlass cannulation was not possible in 1 subject. In those with previously identified strictures, 8/12 had a stricture identified during SpyGlass, 2 as probable malignant and 6 as benign strictures using endoscopic criteria. In those with filling defect, choledocholithiasis was identified in 7 subjects and 1 subject was found to have a villous adenoma. The cholangioscopy was reported normal in 4 subjects (19%). SpyBite biopsies were taken in 10 subjects with histology showing inflammation (n = 5), atypia (n = 2), adenoma (n = 2) and normal (n = 1) giving a biopsy adequacy of 100%. Overall, the SpyGlass evaluation agreed with the histopathologic evaluation of SpyBite-targeted biopsies in 8/10 (80%) cases and therefore a definitive diagnosis was made in 18/21 (86%) patients. There were no serious complications with only 1 case of mild pancreatitis, 1 case of liver abscess (after 2 weeks) and 6/15 patients received prophylactic anti-biotic. Two subjects have had successful surgery for cholangiocarcinoma and all but 1 subjects are alive at the mean follow-up period of 19 months. Conclusion Using the SpyGlass cholangioscope, a definitive diagnosis can be made with a high accuracy in 86% of patients with indeterminate biliary lesions. This is primarily due to direct visualisation and targeted biopsy sampling. Therefore, the SpyGlass system should be considered in all patients with indeterminate biliary lesions. Disclosure of InterestNone Declared.